Respostas
respondido por:
2
Olá!!!
{ x - y = 4
{ x + 2y = 7
Método de substituição!
x - y = 4
x = 4 + y
x + 2y = 7
4 + y + 2y = 7
y + 2y = 7 - 4
3y = 3
y = 3/3
y = 1
x = 4 + y
x = 4 + ( 1 )
x = 4 + 1
x = 5
O par ordenado é ( 5, 1 )
Espero ter ajudado...
{ x - y = 4
{ x + 2y = 7
Método de substituição!
x - y = 4
x = 4 + y
x + 2y = 7
4 + y + 2y = 7
y + 2y = 7 - 4
3y = 3
y = 3/3
y = 1
x = 4 + y
x = 4 + ( 1 )
x = 4 + 1
x = 5
O par ordenado é ( 5, 1 )
Espero ter ajudado...
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás